The Management of Disability in the workplace: a case study of the - Godden, Zini (My University, 2011)
South Africa has made huge strides in the policy process arena, more specifically policy that is directed at addressing the injustices of its Apartheid past. These gains have been predominantly in respect of policy initiation and formulation, evidenced in the number of white paper and policy guidelines throughout the public sector. It is also no secret that many Public Service institutions have been grappling with articulating these policies from statements of intent into viable programmes and projects. Much of this relates to policy management, particularly in respect of managing policy implementation. The purpose of this exploratory study is to determine the extent to which the policy imperatives for the employment of people with disabilities as stated in the White Paper on an Integrated National Disability Strategy (1997) are reflected in the workplace through management frameworks and practices. A qualitative research methodology was used to assess the Management of Disability using the Department of Land Affairs as an insight stimulating example One of the main findings as reflected through the case of the Department of Land Affairs, is that though the Public Service has made some progress in respect of demystifying disability though awareness raising efforts, this has not sufficiently filtered down to impact on effective cross-sectional management of disability. The management of disability is largely confined to the disability desk and in the case of Land Affairs, also the Disability Forum, while employees with disabilities are employed across the department. One of the main conclusions of this study is that policy implementation needs effective political leadership, technical know-how, effective institutional and human resource capacity, amongst others. In the example of the department of Land Affairs this would include the need for the imperative of disability equity to filter to directorates beyond the transformation directorate, to include directorates such as human resource management, human resource development and legal services that have significant interface with the disability management.
MM - P&DM
Keywords: Disabilities; Disabilities in the workplace; Public service